Early Response to Warfarin Initiation and the Risk of Venous Thromboembolism After Total Joint Arthroplasty. Issue 4 (15th February 2018) - Edelstein, Adam I.; Terzaghi, Clara; Nudelman, Brandon; Qin, Charles; Kwasny, Mary; Manning, David W.
Abstract : Background: Venous thromboembolism chemoprophylaxis with warfarin is common after total joint arthroplasty. Early response to warfarin initiation has been theorized to engender a transient increase in the risk of venous thromboembolism. We hypothesized that a rapid rise in the international normalized ratio is a risk factor for venous thromboembolism after total joint arthroplasty. Methods: This study was a retrospective analysis of Medicare patients undergoing elective total joint arthroplasty who were given nomogram-dosed warfarin for venous thromboembolism prophylaxis. Logistic regression was used to assess the relationship between the postoperative rate of change in the international normalized ratio and the occurrence of symptomatic venous thromboembolism within 30 days postoperatively. Results: The study included 948 patients (715 total knee arthroplasty, 233 total hip arthroplasty), of whom 4.4% experienced symptomatic venous thromboembolism within 30 days postoperatively. The change in the international normalized ratio from postoperative day 1 to postoperative day 2 was significantly greater in the symptomatic venous thromboembolism group compared with the group that did not have venous thromboembolism (increase of 0.70 versus 0.46; P = 0.008). Regression analysis showed that a higher rate of change in the international normalized ratio was associated with increased risk of symptomatic venous thromboembolism (odds ratio, 2.59 per unit of change in the international normalized ratio; 95% confidence interval, 1.51-4.38; P = 0.001). Conclusion: A rapid rise in the international normalized ratio after warfarin initiation in total joint arthroplasty patients is associated with increased risk of symptomatic venous thromboembolism. This novel finding identifies a population at risk for this complication. Further study of the early effects of warfarin therapy is warranted. Level of Evidence: Level III